2008
DOI: 10.1007/s12161-007-9001-4
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Sample Preparation for Acrylamide Determination in Cocoa and Coffee Products

Abstract: A modified sample preparation for acrylamide determination in difficult matrices such as cocoa and coffee by a liquid chromatography-tandem mass spectrometry method is presented in this work. For the sample pretreatment, different solvents, purification steps, and solid-phase extraction cartridges were evaluated. The analyses were carried out on a μ-Bondapak C 18 column using acrylamide-D 3 as internal standard. For identification and confirmation of acrylamide, relative retention time and two diagnostic ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Although this study focused on finding a mild and facile laboratory scale route to new 6-methoxy scaffold β-carbolines synthesis, this work might has potential value in controlling the β-carboline formation during food processing. DOE optimisation of organic synthesis condition (Arisseto et al 2008;Erica et al 2013;Farah et al 2012;Jintao et al 2000;Teik Beng et al 2013) showed that temperature and catalyst was significant factors that determine the yield of this Maillard reaction (Figures 2-3). It was evident that both the temperature and time exhibit positive effects on the product yield of 6-methoxytetrahydro-β-carboline.…”
Section: Generalmentioning
confidence: 99%
“…Although this study focused on finding a mild and facile laboratory scale route to new 6-methoxy scaffold β-carbolines synthesis, this work might has potential value in controlling the β-carboline formation during food processing. DOE optimisation of organic synthesis condition (Arisseto et al 2008;Erica et al 2013;Farah et al 2012;Jintao et al 2000;Teik Beng et al 2013) showed that temperature and catalyst was significant factors that determine the yield of this Maillard reaction (Figures 2-3). It was evident that both the temperature and time exhibit positive effects on the product yield of 6-methoxytetrahydro-β-carboline.…”
Section: Generalmentioning
confidence: 99%
“…A modified sample preparation for AA determination in difficult matrices such as cocoa and coffee by a LC-MS-MS was described by Arisseto et al (2008). For the identification and confirmation of AA, relative retention time and two diagnostic ions were monitored.…”
Section: High-performance Liquid Chromatographymentioning
confidence: 99%
“…In past years, a number of chromatographic methods have been developed to determine acrylamide such as gas chromatography (GC) with derivatization and high-performance liquid chromatography (HPLC) without derivatization. , Nowadays, most analytical methods are based on GC-MS and LC-MS/MS, which appear to be acknowledged as the most useful and authoritative methods for the quantification of acrylamide in complex matrices. However, both GC-MS and LC-MS are high-cost and cannot be easily adopted by nonspecialized laboratories.…”
Section: Introductionmentioning
confidence: 99%